Recent improvements of flexible GaN‐based HEMT technology. Issue 4 (3rd February 2017) - Mhedhbi, Sarra; Lesecq, Marie; Altuntas, Philippe; Defrance, Nicolas; Cordier, Yvon; Damilano, Benjamin; Tabares Jimenéz, Gema; Ebongue, Abel; Hoel, Virginie
Abstract : This paper reports on the fabrication and characterization of AlGaN/GaN HEMTs transfered onto two different adhesive flexible tapes. Technological improvements were made during the study concerning thermal conductivity of the tapes as well as the transfer process. In this paper, it is shown that the device transferred onto the tape with higher thermal conductivity exhibits, at V DS = 5 V, a better linear power gain G p by 31.6% (15.8 dB instead of 12 dB), and a power added efficiency PAE rise by 111% (29.6 instead of 14%) associated with an enhancement of saturated power P sat by 281% (420 instead of 110 mW mm −1 ). Optimizing the flexible tape thermal properties and dealing with reliability issues of GaN layer transfer technology, provide a promising way in the frame of flexible electronics, where medium power, high frequency, and flexibility are needed.